Geologi dan Studi Provenance Batupasir Formasi Bentang di Daerah Luyubakti dan Sekitarnya, Kecamatan Puspahiang, Kabupaten Tasikmalaya, Provinsi Jawa Barat - Rizqi, Al Hussein Flowers; Ramadhan, Dimas; Pambudi, Setyo (Retii, 2024)
The research area is administratively located in the Luyubakti area, Puspahiang District, Tasikmalaya Regency, West Java Province. Geographically located at the coordinates of 7Â°29'47.85â€ N - 7Â°24'56.43â€ LS and 108Â°4'33.32â€œ BT - 108Â°7'50.75â€ BT. The purpose of this research is to determine the geological conditions and composition of sandstones of the Bentang Formation in relation with the determination of provenance. The method used is mapping with the concept of lithostratigraphy and petrographic analysis in calculating the sedimentary mineral composition. The results of provenance analysis show that the sandstones of the Bentang Formation in the study area have three main sources of sediment supply in the Bentang Formation, namely Continental Block, Magmatic Arc, and Recycle Orogen.